Identifikasi Kesiapsiagaan Bencana Hidrometeorologi Pada Masyarakat Desa Papahan Kecamatan Tasikmadu Kabupaten Karanganyar - Kusdhiarningsih, Betty; Novitayanti, Eka (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2023)
The Karanganyar Regency Government, Central Java, has 14 out of 17 sub-districts in the Karanganyar region which are areas that are prone to natural disasters, especially during the rainy season. Background: therefore it is important to prepare all disaster tools and their operational functions must be optimal. In addition to this, all disaster officers and volunteers must start preparing themselves to go into the field if needed at any time. However, one thing that should not be forgotten is the preparedness of the community itself. Because the community is the main actor when a disaster occurs. Research objectives: Influence Hydrometeorological Disaster Preparedness in the Community of Papahan Village, Tasikmadu District, Karanganyar Regency. Research method: The method used in this research is a quantitative research method with a descriptive research type. Results and discussion of the research: The preparedness of the people of Papahan Village was obtained from several indicators, namely the community's experience of disasters in the form of community actions when a disaster occurs, community participation in disaster counseling activities, and community preparedness for disasters which include knowledge, attitudes, emergency response plans, defense systems early warning and resource mobilization. Conclusion: based on the analysis of the data that has been done, it can be concluded that the level of community preparedness in facing hydrometeorological disasters is in the ready category.